PENGARUH TEMAN SEBAYA TERHADAP PERILAKU MENYIMPANG SISWA KELAS X SMK SWASTA SATRIA BINJAI TAHUN PELAJARAN 2017/2018 - Sari Wardani Simarmata Fahmi Ilyas Karo Karo (Universitas Islam Negeri Sumatera Utara Medan, 2018)
Purpose of this research is to know the influence of peers on the deviant behavior of class X SMK Binjai Satria Private Lessons Year 2017/2018 .Populasi fifty students, based on the opinions Suharsimi Arikunto when the subject is less than 100 better taken all that research is a population study, based on the opinion of the samples will be taken from the number populasisehingga entire sample in this study amounted to 50 students. This research is a quantitative research. The questionnaire results of peers obtained from the respondents have obtained average value / mean of 52.Hasil questionnaire deviant behavior obtained from the respondents have obtained average value / mean of 59,5.Setelah know that the data collected is valid, then calculation is then performed to test the normality of the data, from the calculation of the normality test has been known that the samples obtained normal distribution, as well as statistical testing was performed using simple linear regression analysis with the testing criteria to test the linearity and regresi.Pada equation significance test research hypotheses, find that the working hypothesis or Ha received r valuecalculated at 0.314 and rtable at 0.284, Because rcount>rtable (0.314> 0.284), we can conclude Ha accepted, that there are Influence Peers Against Deviant Behavior Class X SMK Private Satria Binjai Academic Year 2017/2018